Bistatic radar - Willis, Nicholas J. 1934- (Raleigh, NC SciTech Publishing, 2005)
This book is dedicated on bistatic radar. It summarizes and codifies subsequent bistatic radar research and development. It discusses static radar research and development, defines and resolves many issues and controversies plagung bistatic radar, including predicted performance, monosatic equivalence, bistatic radar cross section and resolution, bistatic Doppler, hitchiking, SAR, ECM/ECCM, and, most importantly, the utility of bistatic radars.
"Corrected and reprinted version of the second edition published by Technology Service Corporation in 1995 and published in the first edition by Artech House"--Title page verso.
Electronic reproduction.
Keywords: Bistatic radar; Electronic books